2014
DOI: 10.1002/clc.22234
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Telemedicine Electrocardiogram Triage for a Regional Public Emergency Medical Service: Is It Worth It? A Preliminary Cost Analysis

Abstract: Background: Telemedicine has been shown to improve quality of health-care delivery in several fields of medicine; its cost-effectiveness, however, is still a matter of debate. Hypothesis: Pre-hospital telemedicine electrocardiogram triage for regional public emergency medical service may reduce costs. Methods: An economic evaluation (cost analysis) was performed from the perspective of regional health-care system. Patients enrolled in the study and considered for cost analysis were those who called the local e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…The first was a cost analysis from the perspective of a regional healthcare system. 172 It was based on the costs incurred by all patients who called the local emergency service in 2012 and had a pre-hospital triage for those with suspected acute cardiac disease (n = 109,750 Another cost analysis of implantable defibrillators was based on an RCT (n = 200). 174 Patients with implantable defibrillators with wireless transmission were randomized between remote monitoring and conventional care and were followed up for 16 months.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…The first was a cost analysis from the perspective of a regional healthcare system. 172 It was based on the costs incurred by all patients who called the local emergency service in 2012 and had a pre-hospital triage for those with suspected acute cardiac disease (n = 109,750 Another cost analysis of implantable defibrillators was based on an RCT (n = 200). 174 Patients with implantable defibrillators with wireless transmission were randomized between remote monitoring and conventional care and were followed up for 16 months.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…Nevertheless, recent evidence shows some potential cost reduction associated with the implementation of telemedicine support. A cost per quality-adjusted life year gain of €1927 was calculated in a regional registry for pre-hospital electrocardiogram diagnosis of ST-elevation acute myocardial infarction [60]. Similarly, an 83$ individual cost saving per year was figured in another emergency setting using telemedicine support [61].…”
Section: Telemedicine: Considerations On Cost-efficacymentioning
confidence: 99%
“…The positive effect of pre-hospital ECG on the outcome of patients with ACS has been repeatedly confirmed in several recent studies reported from around the world [46][47][48][49], including China [50][51][52].…”
mentioning
confidence: 70%